Honey Bee as Alternative Medicine to Treat Eleven Multidrug-Resistant Bacteria Causing Urinary Tract Infection during Pregnancy - Mabrouka Bouacha; Hayette Ayed; Nedjoud Grara (MDPI AG, 2018)
Medicinal benefits of honey bee have been recognized in the medical community since ancient times as a remedy for many diseases and infections. This study aimed to investigate the in vitro susceptibility of 11 multidrug-resistant bacterial strains, isolated from urinary tract infections of pregnant women, to six honey samples collected from different localities in the east of Algeria. The evaluation of the antibacterial activity was performed by the well method followed by the broth dilution method using two-fold dilutions of each honey sample ranging from 2.5 to 80% (w/v). The results obtained in this study revealed that all tested honeys exhibited potent antibacterial activity against the tested strains. The diameters of inhibition ranged from 19.67 to 53.33 mm, with minimum inhibitory concentrations (MICs) ranging from 2.5 to 40% (w/v) and minimum bactericidal concentration (MBCs) varied between 2.5 and 80% (w/v). Gram-positive bacteria were found to be more susceptible than Gram-negative bacteria with diameters ranging from 43.33 to 53.33 mm; MIC and MBC values ranged from 2.5 to 5% (w/v). The P. aeruginosa strain was found to be less susceptible than other strains with inhibitory diameters ranging from 19.67 to 27.33 mm; MICs ranged from 20 to 40% and MBCs ranged from 20 to 80% (w/v). This contribution has provided a broad overview of the antibacterial activity of Algerian honey and shown that honey bee has great potential for therapeutic use as an alternative therapy for urinary tract infection treatment which is safe and efficient during pregnancy.